The Implementation of Scaffolding in Writing Recount Texts in SMP Joannes Bosco Yogyakarta - Dewi, Tiara Maria; Iswandari, Yuseva Ariyani (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2016)
In this research, scaffolding is implemented in English class of the 8th grade students of SMP Joannes Bosco Yogyakarta when they learn about recount text. This research aims to find out the process of how scaffolding is implemented and to know what the benefits of scaffolding in writing recount text. There were two research problems. The first was How is scaffolding for the 8th grade students of SMP Joannes Bosco in writing a recount text? and the second was What are the benefits of scaffolding in writing a recount text in SMP Joannes Bosco Yogyakarta? The writers conducted a descriptive qualitative research in this study. The data was gathered by interviewing the English teacher, writing on the field notes, distributing the questionnaires, and interviewing the students. Analyzing the students writings was used as the supplementary data to make the result stronger. The result of this study showed that the implementation of scaffolding gave benefits for the students. The benefits were challenging the students through deep learning and discovery, engaging the students in meaningful and dynamic discussions in the small and the large classes, and motivating the learners to become better students. In conclusion, scaffolding does give benefits for the students so that teachers are able to use scaffolding as one of the effective teaching techniques.